Theoretical investigation of the tautomerism of isoorotic acid in gaseous and aqueous phases - Cho, Seung Joo; Mohamed, Adel A.; Elroby, Shaaban A. K. (WILEY, 2007)
In the present investigation, the tautomeric and conformational equilibrium of isoorotic acid have been studied using Moller-Plesset second-order (MP2) and density functional theory (DFT) methods in the gas phase and aqueous solution (epsilon = 78.5) using the IPCM model. The relative energies of these tautomers have been calculated at the two levels of theory using 6-311++G** basis set. Energetics and relative stabilities of the tautomers; were compared and analyzed in both the gaseous and aqueous phases. The results indicate that the diketo tautomer (iso) is the most stable form in the gas phase and water. The carboxylic substitution in the uracil ring does not alter its relative stability order of the tautomers. The proton affinity of the oxygen atoms and the deprotonation enthalpy of the NH bonds of isoorotic acid have been compared with recent data of uracil. The relative stability of both syn- and anti-conformations was investigated and the syn form was found to be more stable by 17.65 kcal/mol. It was determined in ab initio calculations that an electron can attach to isoorotic acid, forming a stable anion better than uracil. (C) 2006 Wiley Periodicals, Inc.
Keywords: INITIO QUANTUM-MECHANICS; GAS-PHASE; ELECTRON CORRELATION; EQUILIBRIA; URACIL; THYMINE; 3-HYDROXYPYRAZOLE; STABILITIES; PROTONATION; AFFINITIES